Distributed Cooperative Precoding with Power Control for Cellular Systems with Correlated Antennas at the Receiver. (28 December 0201) - James J. James J., Vinosh Babu Vinosh Babu; Ramamurthi Ramamurthi, Bhaskar Bhaskar; Venkatraman Venkatraman, Ganesh Ganesh
Abstract : We consider the problem of cooperative precoding working alongside an antenna power allocation algorithm in the downlink of a correlated Multiple Input and Multiple Output (MIMO) interference channel. An analytical model for the multicell, multiuser system with receiver-side correlation is analyzed for a realistic system configuration having two antennas each at the basestation and user terminal. Based on the precoder choices of the different terminals and the per-antenna power levels requested, a criterion is proposed for maximizing the received SINR of a severely interference-limited cell-boundary user, while controlling the loss in performance of high-SINR in-cell users in the system. A distributed protocol for cooperation amongst the base stations is also proposed. System performance gains measured in terms of mean and cell-edge spectral efficiency values are provided using numerical simulations. An improvement of about 28% to the mean spectral efficiency and 115% to the cell-edge spectral efficiency is reported over single-cell beamforming. We also demonstrate that terminals with high receive-side correlation form a specific use case of this algorithm. With two antennas at the receiver and 0.9 correlation factor, an improvement of 37% in the mean spectral efficiency is reported. The proposed technique takes into account practical constraints such as limiting to a modest level the information exchanged from the user equipments to the serving base station and amongst the base stations.